Toward Routine Minimally Invasive Ventricular Septal Defect Closure Via Right Lateral Minithoracotomy - Aydin, Selim; Temur, Bahar; Basgoze, Serdar; Guzelmeric, Fusun; Guvenc, Osman; Erek, Ersin (Frontiers in Pediatrics, 2021)
Background: Improving the surgical results and recent advancement of transcatheter techniques for closure of ventricular septal defect (VSD), increased the demand for minimally invasive approaches. In this study, we analyzed the the results of the patients who underwent VSD closure with right lateral minithoracotomy (RLMT). Methods: Between September 2014 and February 2021, 24 patients underwent minimally invasive VSD closure with RLMT. Median age of the patients was 16 months (range, 4 to 84 months). Fifteen patients (62.5%) were female. Median weight of the patients was 9.75 kg (range, 4.6 to 30 kg). The type of VSDs were perimembranous (PM) in 19 patients, subaortic in 3 patients, inlet in 1 patient and subpulmonic in 1 patient. Five patients had low-lying pulmonary stenosis (PS) in addition to VSD. Results: No perioperative death or major complication occured during the follow-up. All defects were repaired through RLMT. The median cardiopulmonary bypass time was 81 minutes (range, 44 to 163 minutes), and aortic cross clamp time was 65 minutes (range, 33 to 131 minutes). The median hospital stay was 6 days (range, 5 to 21 days). One patient had minimal (2 mm) residual left-to-right shunt. All families were satisfied with the cosmetic results during the follow-up. Conclusions: The RLMT method is a safe and effective alternative to standard median sternotomy for VSD closure and can be performed with favorable cosmetic and clinical results.